Perspektif Konstitusional Kedudukan Negara dan Swasta dalam Pengelolaan Sumber Daya Air Menurut UUD 1945 - Kasim, Helmi; Anindyajati, Titis (Mahkamah Konstitusi Republik Indonesia, 2016)
This research discusses the constitutional perspective of water resources management and its relation to the position of the state and the private sector in the management of water resources. This research examines the decision of the Constitutional Court in the judicial review of Law No. 7 of 2004 on Water Resources. There are two issues discussed in these studies namely (i) what is the constitutional perspective of water resource management and (ii) what is the position of the state and the private sector in water resources management? This research uses normative law research. The results showed that there are two constitutional perspectives in water resources management which are the perspective of control by the state under Article 33 paragraph (3) and the perspective of Human Rights perspective based on Article 28H of the 1945 Constitution. Based on the perspective of control by the state, management of water resources should be controlled by the state from upstream to downstream. The state should take control of water resources and establish distribution channels to meet the needs of the citizens on the water. From a human rights perspective, the state is obliged to protect, promote and fulfill the right to water. This obligation cannot be left to the private sector especially in water management based on its primary function. Therefore, the overall water management should be done by the state through the State Owned Enterprises or Regional Owned Enterprises. In fact, the monopoly of water management is a policy option that can be taken by the state. On the other hand, the private sector can take a part to commercialize water based on the use of water in its secondary function for industrial use through licensing mechanism. The study concluded that the state has an obligation to meet the citizens’ rights to water in order to meet the needs of a decent life based on primary functions of water. Secondary functions can be operated by private sectors.